Detecting the molecular basis of phenotypic convergence. Issue 11 (23rd August 2018) - Chabrol, Olivier; Royer‐Carenzi, Manuela; Pontarotti, Pierre; Didier, Gilles
Abstract: Convergence is the process by which several species independently develop similar traits. This evolutionary process is not only strongly related to fundamental questions such as the predictability of evolution and the role of adaptation, its study also may provide new insights about genes involved in the convergent phenotype. We focus on this latter question and aim to detect the molecular basis of a given phenotypic convergence. After pointing out a number of concerns with current detection methods based on ancestral reconstruction, we propose a novel approach combining an original measure, called convergence index, which associates to any proteic site a quantity reflecting the extent to which it supports a phenotypic convergence, with a statistical framework for selecting genes from the convergence indices of all their sites. First, our measure of the "convergence level" outperforms two previous ones in distinguishing simulated convergent sites from nonconvergent ones. Second, by applying our detection approach to the well‐studied case of convergent echolocation between dolphins and bats, we identified a set of genes which is very significantly annotated with audition‐related GO terms. This result constitutes an indirect evidence that genes involved in a phenotypic convergence can be identified with a genome‐wide approach, a point which was highly debated, notably in the echolocation case. Our approach paves the way to systematic studies of numerous examples of convergent evolution in order to link convergent phenotypes to genotypes.